THE RELATIVE EFFECTS OF PRESSURE, TEMPERATURE AND OXYGEN FUGACITY ON THE SOLUBILITY OF SULFIDE IN MAFIC MAGMAS - PART 1. THE LIQUIDUS RELATIONS OF THE FE-RICH PORTION OF THE FE-NI-S SYSTEM FROM 30 TO 100 KB - Mavrogenes J.A.; O'Neill H.S.C. (My University, 1999)
The sulfur contents at sulfide saturation (SCSS) of a basaltic and a picritic melt have been measured experimentally as a function of pressure and temperature from 5 to 90 kb and 1400-1800°C, using piston-cylinder and multi-anvil solid media pressure devices. Three distinct regimes of oxygen fugacity were investigated, imposed by the use of Fe100, Fe40Ir60, and Fe20Ir80 capsules. The compositions of quenched run products, including the S contents of the silicate glasses, were determined by electron microprobe analysis. Theoretical considerations suggest that SCSS values (in ppm) can be described by an equation of the form: ln[S/ppm]SCSS=AT+B+CPT+ln aFeSsulfide where A and B are functions of the composition of the silicate melt. This equation implies that SCSS is independent of fO2 and fS2, except insofar as these factors influence the nature of the sulfide liquid (hence aFeSsulfide). The experiments reported here confirm this. The SCSS of both the basaltic and picritic compositions are rather insensitive to temperature, but show a strong exponential decrease with increasing pressure. Consequently, a magma generated in equilibrium with residual sulfide in the mantle becomes under saturated in sulfide during adiabatic ascent. At low pressure, sulfide saturation should occur only after substantial crystallization, under closed-system conditions, or after significant modification via assimilation (e.g., of S-rich sediments).